2008
DOI: 10.1245/s10434-007-9748-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Among Five-Year Survivors After Treatment for Very Low Rectal Cancer With or Without a Permanent Abdominal Stoma

Abstract: After five years, cancer-free patients operated on for low or very low rectal cancer have a better QOL if a definitive terminal abdominal stoma was avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 27 publications
5
67
1
3
Order By: Relevance
“…Some studies have shown that persons with ostomies have worse HRQOL than their counterparts with anastamosis [4][5][6][7] ; other studies show similar or mixed HRQOL across…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that persons with ostomies have worse HRQOL than their counterparts with anastamosis [4][5][6][7] ; other studies show similar or mixed HRQOL across…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted by showed Jansen et al (2010) that colorectal cancer survivors who have been living with the disease for more than five years indicated that their overall domains of quality of life were better than those who had ived with it for under five years. The other study demonstrated that ostomy patients with more than two years experience had shown a better quality of life (Fucini et al, 2008;Sales et al, 2014). It is understandable that the more time the survivors live for, the more chance there is to learn and adjust to the new conditions of living with cancer and stoma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One may argue that QoL of the patients with a stoma may be affected by the complicated postoperative course and by the second urgent operation as well. Nevertheless it is well established that the presence of a stoma can have detrimental effects on QoL, even in long-term studies (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…All the patients were administered with a QoL questionnaire widely used in colorectal surgery (EORTC QLQ CR-38) (20)(21)(22)(23)(24) prior to discharge and at 1-month follow-up.…”
Section: Methodsmentioning
confidence: 99%